Slug Feeding Triggers Dynamic Metabolomic and Transcriptomic Responses Leading to Induced Resistance in Solanum dulcamara - Calf, Onno W.; Lortzing, Tobias; Weinhold, Alexander; Poeschl, Yvonne; Peters, Janny L.; Huber, Heidrun; Steppuhn, Anke; van Dam, Nicole M. (Frontiers in Plant Science, 2020)
Induced plant responses to insect herbivores are well studied, but we know very little about responses to gastropod feeding. We aim to identify the temporal dynamics of signalling- and defence-related plant responses after slug feeding in relation to induced resistance. We exposed Solanum dulcamara plants to feeding by the grey field slug (GFS; Deroceras reticulatum) for different periods and tested discs of local and systemic leaves in preference assays. Induced responses were analysed using metabolomics and transcriptomics. GFS feeding induced local and systemic responses. Slug feeding for 72h more strongly affected the plant metabolome than 24h feeding. It increased the levels of a glycoalkaloid (solasonine), phenolamides, anthocyanins, and trypsin protease inhibitors as well as polyphenol oxidase activity. Phytohormone and transcriptome analyses revealed that jasmonic acid, abscisic acid and salicylic acid signalling were activated. GFS feeding upregulated more genes than that it downregulated. The response directly after feeding was more than five times higher than after an additional 24h without feeding. Our research showed that GFS, like most chewing insects, triggers anti-herbivore defences by activating defence signalling pathways, resulting in increased resistance to further slug feeding. Slug herbivory may therefore impact other herbivores in the community.